Sensitivity, Specificity, and Safety of a Novel ESAT6-CFP10 Skin Test for Tuberculosis Infection in China: 2 Randomized, Self-Controlled, Parallel-Group Phase 2b Trials. (22nd May 2021) - Xu, Miao; Lu, Wei; Li, Tao; Li, Jingxin; Du, Weixin; Wu, Qi; Liu, Qiao; Yuan, Baodong; Lu, Jinbiao; Ding, Xiaoyan; Li, Feng; Liu, Min; et al.
Abstract: Background: Diagnostics to identify tuberculosis infection are limited. We aimed to assess the diagnostic accuracy and safety of ESAT6-CFP10 (EC) skin test for tuberculosis infection in Chinese adults. Methods: We conducted 2 randomized, parallel-group clinical trials in healthy participants and tuberculosis patients. All participants were tested with the T-SPOT.TB test, then received an EC skin test and tuberculin skin test (TST). The diameter of skin indurations and/or redness at injection sites were measured at different time periods. A bacillus Calmette Guerin (BCG) model was established to assess the diagnosis of tuberculosis infection using an EC skin test. Results: In total, 777 healthy participants and 96 tuberculosis patients were allocated to receive EC skin test at 1.0 μg/0.1 mL or 0.5 μg/0.1 mL. The area under the curve was 0.95 (95% confidence interval [CI], .91–.97) for the EC skin test at 1.0 μg/0.1 mL at 24–72 hours. Compared with the T-SPOT.TB test, the EC skin test demonstrated similar sensitivity (87.5, 95% CI, 77.8–97.2 vs 86.5, 95% CI, 79.5–93.4) and specificity (98.9, 95% CI, 96.0–99.9 vs 96.1, 95% CI, 93.5–97.8). Among BCG vaccinated participants, the EC skin test had high consistency with the T-SPOT.TB test (96.3, 95% CI, 92.0–100.0). No serious adverse events related to the EC skin test were observed. Conclusions: The EC skin test demonstrated both high specificity and sensitivity at a dose of 1.0 μg/0.1 mL, comparable to the T-SPOT.TB test. The diagnostic accuracy of the EC skin test was not impacted by BCG vaccination. Clinical Trials Registration: NCT02389322 and NCT02336542. Abstract : Current diagnostics for tuberculosis infection are limited. We evaluated the ESAT6-CFP10 skin test and found a good safety profile and high diagnostic accuracy. It may be a viable option, especially in low-income countries with universal bacillus Calmette Guerin vaccination.